1977
DOI: 10.1111/j.1550-7408.1977.tb05302.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Sex on the Acquisition of Immunity to Toxoplasmosis in Cats*

Abstract: The effects of age and sex of the cat on oocyst shedding, multiplication of Toxoplasma gondii in tissues of cats, and acquisition of immunity were investigated after oral inoculation of cats with Toxoplasma cysts. Twenty-five cats varying in age from 1 week to 39 months were killed 7-97 days after inoculation with T. gondii. Homogenates of brain, heart, mesenteric lymph nodes, retina, and blood from these cats were inoculated into mice to test for Toxoplasma infectivity. Toxoplasma was isolated more frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 9 publications
1
17
0
2
Order By: Relevance
“…Nevertheless, seroprevalence of infection in domestic cats has been found to vary with their lifestyle (wild, stray or domestic), age, serological test used and geographical location (Gauss et al, 2003). Cats of all ages, gender and breeds are susceptible to infection (Dubey et al, 1977;Dorny et al, 2002). In the present study, the odds of a cat being seropositive increased by an average factor of 1.58 for each 1-year increase in age.…”
Section: Discussionsupporting
confidence: 48%
“…Nevertheless, seroprevalence of infection in domestic cats has been found to vary with their lifestyle (wild, stray or domestic), age, serological test used and geographical location (Gauss et al, 2003). Cats of all ages, gender and breeds are susceptible to infection (Dubey et al, 1977;Dorny et al, 2002). In the present study, the odds of a cat being seropositive increased by an average factor of 1.58 for each 1-year increase in age.…”
Section: Discussionsupporting
confidence: 48%
“…Cat bioassays have not provided any clear evidence of sex-bias in the occurrence of toxoplasmosis [19]. However, experimental studies in mice have shown that females are more susceptible than males to T. gondii infection and develop more severe cerebral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The male sex hormone testosterone (Te) is known to promote a wide variety of diseases including different forms of cancer such as prostate-and hepatocarcinoma (Henderson et al 1982, Kemp, Leary & Drinkwater 1989 as well as to aggravate the course and outcome of infectious diseases by parasites (Alexander & Stimson 1988). Indeed, there is vast literature available that Te increases the susceptibility of vertebrate hosts towards many different protozoan parasites (Kierszenbaum et al , Dubey, Hoover & Walls 1977, Greenblatt & Rosenstreich 1984 and helminthic endoparasites (Dow & Jarrett 1960, Dobson 1962, Miller 1965, Ohbayashi & Sakamoto 1966, Charniga et al 1981, Bone & Bottjer 1986. Te even increases the susceptibility towards arthropod ectoparasites such as ticks (Ali & Sweatman 1966).…”
Section: Introductionmentioning
confidence: 99%